Endoscopic Band Ligation for Treatment of Bleeding Internal Hemorrhoids in Primary Referral Hospital - Zein, Ahmad Fariz Malvi Zamzam; Luthfi, Ahmad Ichwan; Pratiwi, Lusi; Adi, Galang Prasetyo (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Aim: This study aims to evaluate the efficacy and safety of endoscopic band ligation (EBL) for bleeding grade III internal hemorrhoids in an evidence-based case report.Method: A search was conducted on PubMed and Cochrane databases based on clinical query, with keywords "endoscopic band ligation AND internal hemorrhoids". The inclusion criteria were meta-analysis, systematic review and randomized clinical trial, and written in English. The critical appraisal was performed for validity, importance, and applicability.Results: Of 18 studies, only 2 studies that suited the criteria. Compared to bipolar electrocoagulation (BPEC), EBL had significantly higher success rate in controlling bleeding and reducing the grade of hemorrhoids. In comparison with band ligation with rigid proctoscope (BL-RP), EBL was associated with higher success rate, lesser treatment sessions, and earlier symptom control. Mild complications and symptomatic recurrence were comparable among EBL, BPEC, and BL-RP.Conclusion: Endoscopic band ligation is effective and safe for bleeding grade III internal hemorrhoids. It is feasible procedure in primary referral hospital.